Giant reversible magnetocaloric effect in MnNiGe-based materials: Minimizing thermal hysteresis via crystallographic compatibility modulation. (1st August 2019) - Liu, Jun; Gong, Yuanyuan; You, Yurong; You, Xinmin; Huang, Bowei; Miao, Xuefei; Xu, Guizhou; Xu, Feng; Brück, Ekkes
Abstract: MnMX (M = Co or Ni, X = Si or Ge) alloys with strong magnetostructural coupling exhibit giant magnetic entropy change and are currently extensively studied. However, large thermal hysteresis results in serious irreversibility of the magnetocaloric effect in this well-known system. In this work, we report a low thermal hysteresis and large reversible magnetocaloric effect in a MnNiGe-based system. The introduction of Fe into both Ni and Mn sites can establish stable magnetostructural transitions from paramagnetic hexagonal to ferromagnetic orthorhombic phases. Fascinatingly, a low thermal hysteresis of 5.2 K is achieved in Mn0.9 Fe0.2 Ni0.9 Ge alloy with a large magnetization difference of 62.1 A m 2 /kg between the two phases. These optimized parameters lead to a partially reversible phase transformation under a magnetic stimulus and bring about a large reversible magnetic entropy change of −18.6 Jkg −1 K −1 under the field variation of 0–5 T, which is the largest value reported in MnMX system up to now. Moreover, this low-hysteresis magnetostructural transformation and large reversible magnetocaloric effect can be tuned by doping with Si in a wide temperature range covering room temperature. We also introduce geometrically nonlinear theory to discuss the origin of low hysteresis in MnMX alloys. A strong relation is found between thermal hysteresis and the change of c axis in the orthorhombic structure during the transition. Our work greatly develops the potential of MnMX alloys as magnetocaloric materials and is meaningful to seek or design a MnMX system with low thermal hysteresis. Graphical abstract: Image 1